ANALYSIS OF GREEN PROTECTIONISM AGAINST THE BARRIERS OF INDONESIA’S CRUDE PALM OIL (CPO) EXPORT IN THE EUROPEAN UNION - Adhitya Anggriawan Wisadha, Made; Surya Dharma Jaya, Ida Bagus (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015, 2015)
This article analyzed concerning Green Protectionism against the Barriers of Indonesia’s Crude Palm Oil (CPO) Export in the European Union in accordance with GATT / WTO provisions. This writing is a normative legal research that used statutory, fact, and case approaches. In the analysis, it will explore the policy of green protectionism and look at various existing legal instruments, inter alia GATT/WTO Agreements, regulating the legal issue in concern.
Keywords: Green Protectionism, Crude Palm Oil, the Provisions of GATT/WTO